A Comparative Study of Performance of SHGs Promoted by NGO and Panchayat (Indian Journal of Extension Education, 2014)
SHG is a very strong instrument to improve socio -economic standard of living, specially for the people living under the poverty line and in the rural area. In such situation, a comparative research study was conducted in Tamluk sub-division of Purba -Midnapur district in West Bengal to determine the relative difference of the performance by the SHGs (panchayat promoted and NGO promoted SHGs) and impact analysis of micro finance programme. Data were collected with the help of structured interview schedules through personal interview method. The data were processed into frequency and percentage. No significant differences were found between them in terms of their overall performances. However, the NGO-led SHGs performed better than panchayat-led SHGs in case of attributes like purpose of group formation